Ovarian Epithelial Cancers: A Pathological Study of 164 Cases - Intisar Pity; Ghasaq Kareem; Dildar Musa; Abdulkareem Sulaiman; Shang Salih Amedi; Hayam Rasoul; Yasmine Abdalwahab; Dani Hayder (Al-Anbar Medical Journal)
Background: Foremost, the diagnosis of ovarian carcinoma is light microscopic in nature. However high-graded tumors and some equivocal cases may require contemporary tests.Objectives: To examine ovarian carcinoma types in Duhok-Iraq using morphology and available immunohistochemical panels.Materials and Methods: In this retrospective cross-sectional study, paraffin blocks of 164 ovarian carcinoma cases were retrieved from Duhok pathology centers between January 2012 and December 2022. Tumor microsections were taken from these paraffin blocks, stained with Hematoxylin and Eosin (H&E), and examined under the light microscope. After morphologic diagnosis, tumors were classified. High-grade and equivocal cases were subjected to different immunohistochemical panels depending on the light microscopical morphology and the available antibodies. The immunohistochemical technique applied was the automated immune-stainer (Dako-Denmark) on deparaffinized tumor sections using the avidin-biotin–peroxidase complex technique.Results: The study cases included 125 primary and 39 metastatic carcinomas. All women were over 20 years with a mean age of 42.8 years. Among the primary tumors, high-grade serous carcinoma (33.5%) was the commonest, followed by mucinous carcinoma (22.6%), endometrioid carcinoma (14%), clear cell carcinoma (2.4%) and transitional cell carcinoma (1.2%). The remaining primaries comprised 4 (2.4%) Malignant Mixed Mullerian tumor. The 39 metastatic carcinomas were adenocarcinomas, average age was 36.9 years. Sites of origin included: 18 colonic (including appendix), 7 gastric, 4 endometrial, 5 breast, 3 pancreatobiliary, and 2 ampullary carcinomas.Conclusion: High grade serous carcinoma topped the list of ovarian carcinoma cases (primary and metastatic). Diagnosis of most carcinoma cases was made using routine H&E light microscopic sections. Difficulties arise in high-grade and metastatic cases, particularly cases exclusive to an ovary. Metastatic cases have primarily emerged from the colon (including appendix), stomach, endometrium, pancreatobiliary, breast, and ampulla. Such cases need contemporary tests, like immunohistochemistry.